Lehman Brothers - McDonald, Oonagh (Manchester University Press, 2021)
"On September 12th 2008, Lehman Brothers was valued at 639 billion US dollars. On Monday 15th September, it was worth nothing. How could trillions of dollars seemingly melt into air? Lehman Brothers had a long and prestigious history, and certainly until the end of 2007 had appeared to be conducting a very successful business. Its collapse was the largest bankruptcy in American history and is widely regarded as a crucial event in triggering the turmoil in the markets that triggered the global financial crisis.